A Cross-Sectional Study on the Impact of Synchronous Learning among Medical Students during Covid 19 Pandemic: A Case Study of SKZMC, Lahore - Anwar, Muhammad Imran; Naeem, Muhammad Tayyab; Aamir Jameel, Muhammad; Jameel, Hafsa; Tahir, Sameen (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the impact of synchronous learning on medical students of the SKZMC. Place and duration of study: The study was carried out at SKZMC during the month of May 2021. Methodology: A questioner was developed on Google and sent to the medical students of each year of the SKZMC. Data of the 101 duly filled forms was analyzed by using SPSS software. Results: Results of the study reveal that online learning is a new entity for 82.2% medical students and they have not experienced it before. 53.4% participants felt headache during synchronous learning. 42.6% students are of the opinion that online learning method provides an opportunity for real time discussion, 18.8% thinks that it is cost effective, 24.8% for immediate feedback. 77.2% medical students were unable to study during Covid 19. 24.8% students opined that students show misbehavior during online learning. Conclusion: Having real time teacher-students discussion in cost effective manner and knowledge clarity due to immediate feedback enhances the applicability of this technology bound learning methodology. Inability of synchronous learning to develop clinical skills in future physicians with time constraints along with student misbehavior are some pitfalls in this newly implemented learning strategy. Online learning is not only more effective than traditional classroom learning but it is also significantly more cost effective than the tradition way of learning.